English-learning infants’ perception of word stress patterns - Skoruppa, Katrin; Cristià, Alejandrina; Peperkamp, Sharon; Seidl, Amanda (My University, 2011)
Adult speakers of different free stress languages (e.g., English, Spanish) differ both in their sensitivity to lexical stress and in their processing of suprasegmental and vowel quality cues to stress. In a head-turn preference experiment with a familiarization phase, both 8-month-old and 12-month-old English-learning infants discriminated between initial stress and final stress among lists of Spanish-spoken disyllabic nonwords that were segmentally varied (e.g. [ˈnila, ˈtuli] vs [luˈta, puˈki]). This is evidence that English-learning infants are sensitive to lexical stress patterns, instantiated primarily by suprasegmental cues, during the second half of the first year of life.